Hydrogeochemistry and microbial geochemistry of different depth aquifer sediments from Matlab Bangladesh: relation to arsenic contamination in groundwaters - Kibria, Md. Golam (Kansas State University, 2014)
The incidence of high arsenic (As) and other oxyanions (e.g. Mn) has been examined in a ~410km[superscript]2 areas within the Bengal Delta between North and South Matlab, Bangladesh. The aim of this study was to examine the role of sediment geochemistry, coupled with microbial community studies and their relations with different colors and grain sizes of sediments, in determining evolved groundwater hydrochemistry within the aquifers in Matlab. Groundwaters are Ca–Mg–HCO[subscript]3- types in shallow aquifers, Mg-HCO[subscript]3- in the intermediate depths and Na-K-Cl rich in the deeper aquifers. Dissolved As concentration is high (~781μg/l) associated with shallow grey and dark grey sediments, whereas light grey sediments at intermediate depths contain lower As (<10 μg/l). Dissolved Fe[superscript]T on other hand in both sediment types (light grey and grey) shows good correlation with dissolved SO[subscript]4[superscript]2-. In plots of [delta]δ[superscript]18O vs [delta]δD, intermediate and deeper depth aquifer waters plot on the arrays for LMWL and GMWL, which indicates the principal recharge mechanism is likely to be from local precipitation within the shallow aquifers. Only the high As groundwaters deflect from the LMWL, indicating that recharge might be a mixture of precipitation and surficial discharges / infiltrations for these waters. Bulk extraction of sediments showed that grey and dark grey sediments from shallow depths have higher As concentrations (~31 mg/kg) and light grey sediments have comparatively less (~11mg/kg). Sequential extractions for sediment fractionations showed that most of the As was bound to amorphous and poorly crystalline hydrous oxides of Fe and Al phases. Synchrotron-aided bulk-XANES studies conducted on sediments revealed As and S speciation in the core samples at different depths indicating the occurrences of hotspots of As distributed randomly in light grey and grey sediments. As[superscript]3+ is the dominant species in Matlab sediments. More than 101 bacterial families were identified among the eight sediment samples from the South Matlab core and out of them fewer than six families comprised more than ~80% of total bacterial families. Our results indicate significant relationships between bacterial community structure, grain size fractionation, dissolved As concentration and sediment C, Mn, and Fe concentrations for these samples. Groundwater abstracted from these light grey sediments, in contrast to reduced greyish to dark greyish sediments, contain significantly lower amounts of dissolved As and can be a source of safe water for the future. Our work demonstrates that intermediate depth light grey sediments have geochemical and microbial features conducive with safe drinking water for the future.
Keywords: Bangladesh; Matlab; Arsenic; Hydrogeology; Geochemsitry; Geochemistry (0996)